2015
DOI: 10.15517/rbt.v46i4.20683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Trypanosoma lewisi</i> (Kinetoplastida: Trypanosomatidae) on the infection of white rats with <i>Toxoplasma gondii</i> (Eucoccidia: Sarcocystidae) oocysts

Abstract: White rats were inoculated with 10 6 trypomastigotes of Trypanosoma lewisi, simultaneously or two days before and after inoculation with 10 5 oocysts of T. gondií. A greater number of cysts was found in the brain of the animals having concomitant inoculations, as compared with rats inoculated with either one of the two parasites. An apparent immunosuppressive effec! is Iikely. Since both orgartisms can be found in rats, ít is possible that infections with T. lewisi, could make this rodent another intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Infection by Trypanosoma lewisi does not have any direct pathogenic effect on X. cheopis (Table 1); however, this trypanosomiasis may indirectly cause some harm to rodents. Under experimental conditions, T. lewisi was found to increase the multiplication of Toxoplasma gondii in white rats [12,13]. This finding deserves greater attention, since (a) rats infected with T. gondii are considered important in the epidemiology of toxoplasmosis because they can serve as reservoirs of infection for pigs, dogs, and cats; and (b) T. gondii infection may enhance the likelihood of infected rats being predated by cats.…”
Section: Reproduction Of Pathogen In Fleamentioning
confidence: 99%
“…Infection by Trypanosoma lewisi does not have any direct pathogenic effect on X. cheopis (Table 1); however, this trypanosomiasis may indirectly cause some harm to rodents. Under experimental conditions, T. lewisi was found to increase the multiplication of Toxoplasma gondii in white rats [12,13]. This finding deserves greater attention, since (a) rats infected with T. gondii are considered important in the epidemiology of toxoplasmosis because they can serve as reservoirs of infection for pigs, dogs, and cats; and (b) T. gondii infection may enhance the likelihood of infected rats being predated by cats.…”
Section: Reproduction Of Pathogen In Fleamentioning
confidence: 99%
“…Parasitism in wild animals is common and rodents in the wild are highly likely to be infected with multiple pathogens. Thus, understanding the immune responses in relation to co-infection of T. gondii with other pathogens has great potential to be both interesting and relevant in nature (Catarinella et al ., 1998; Onah and Wakelin, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosoma lewisi can have prevalences of up to 56% rats (Liu and Liu, 1990; Desquesnes et al ., 2002; Dobigny et al ., 2019) and has also been considered as pathogenic to humans (Lun et al ., 2009; 2015; Truc et al ., 2013; Lin et al ., 2015). Many previous studies have suggested that T. lewisi infection could induce an immunosuppressive effect on its hosts, resulting in a greater susceptibility to infection by other pathogens, including Salmonella typhimurium, Cryptococcus neoformans and Toxoplasma gondii (Nielsen et al ., 1978; Catarinella et al ., 1998; Gross et al ., 2006; Carrera et al ., 2009). Trypanosoma musculi has similar biological characteristics to T. lewisi but restricted to mice and can also induce an effect on experimental infection of mice with Toxoplasma (Albright and Albright, 1980; Piccolo-Johanning et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation